Congenital heart disease complexity and childhood cancer risk. Issue 17 (16th October 2018) - Collins, R. Thomas; Von Behren, Julie; Yang, Wei; Carmichael, Suzan L.; Reynolds, Peggy; Fisher, Paul G.; Shaw, Gary M.
Abstract : Background: Childhood cancer is increased in those with birth defects, including those with congenital heart disease (CHD). Lymphoma risk is increased in children with CHD. This study analyzes the effect of CHD and CHD severity on childhood cancer risk. Methods: We analyzed cancer risk in a population‐based cohort of children with and without CHD born between 1988 and 2004 by linking data from the California Birth Defects Monitoring Program with data from the California Cancer Registry. We compared cancer risk in children with and without CHD, excluding children with chromosomal anomalies. Results: Of >3 million children in the birth cohort, 65, 585 had birth defects (2%), 25, 981 with CHD. Cancer occurred in 4, 781 (0.15%) children, 43 (0.17%) with CHD. Cancer risk in CHD was increased (hazard ratio [HR]) 2.63, 95% CI: 1.95, 3.55). Leukemia was the most common cancer in those without CHD (1, 722/4, 738, 36%), central nervous system tumors were second (1, 073/4, 738, 23%), and lymphoma third (410/4, 738, 9%). Among children with CHD, lymphoma and leukemia occurred with the same frequency (12/43, 28% for each). HR for lymphoma was 8.37 (CI: 4.71, 14.86) with CHD versus without. HR for leukemia was 2.05 (CI: 1.16, 3.61) with CHD versus without. CHD complexity was higher in lymphoma (3, interquartile range [IQR]: 2–3) than those with leukemia (1, IQR, 1–2; p < .02). Conclusion: Cancer risk is increased in children with CHD. Lymphoma risk is increased in CHD and is correlated with more complex CHD. These results suggest a shared developmental origin for CHD and lymphoma may be present.